DESCRIPTION OF RISK FACTORS IN OCCURRENCE OF PIDIC INFLAMMARY DISEASE IN WOMEN OF REPRODUCTIVE AGE - Dwi Ghita; Umi Kalsum (International Journal of Medicine and Health, 2022)
Pelvic inflammatory disease is a reproductive system disorder in women that can be caused by viruses or bacteria. Pelvic inflammatory disease is an inflammatory process of the female genital organs in the pelvic cavity, namely the genital tract consisting of the uterus, fallopian tubes and surrounding areas including the peritoneum. It is caused by Neisseria gonorrhoeeae or Chlamidia trachomatis and may be the organism involved in bacterial vaginosis. Objective: This study aims to describe the risk factors for pelvic inflammatory disease experienced by women of childbearing age. Research methods; This study uses an analytical survey. The population in this study were all cases of GSR who were treated in hospitals. Andi Makkasau, Parepare City with a total of 247 people. The sampling technique was purposive sampling. The method of data collection in this study is secondary data, namely if the desired data collection is obtained from other people or other places and is not carried out by the researcher himself where in this study the researcher records the register number of patients with pelvic inflammation (PRP) obtained from the register book at the GSR treatment room or medical record. Then take the patient's status on the medical record at Andi Makkasau Hospital. After that, take the data and select the complete data based on the specified criteria. The data were analyzed using chi-square. namely if the desired data collection is obtained from other people or other places and is not carried out by the himself where in this study the researcher records the register number of patients with pelvic inflammation (PRP) obtained from the register book at GSR treatment room or medical records. Then take the patient's status on the medical record at Andi Makkasau Hospital. After that, take the data and select the complete data based on the specified criteria. The data were analyzed using chi-square. namely if the desired data collection is obtained from other people or other places and is not carried out by the himself where in this study the researcher records the register number of patients with pelvic inflammation (PRP) obtained from the register book at GSR treatment room or medical records. Then take the patient's status on the medical record at Andi Makkasau Hospital. After that, take the data and select the complete data based on the specified criteria. The data were analyzed using chi-square.